(untitled) (Research, Society and Development, 2021)
Studies have been conducted to verify the effects of biomaterials such as platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) and their contribution to the wound healing process by releasing growth factors that have properties of tissue regeneration. Many evidences are also favorable to the topical use of rosuvastatin (RSV) in skin lesions, by positively modifying the basal tissue blood flow. However, it is unclear whether this effect is involved in increased blood flow and consequently an improvement in the healing process. In this sense, the present study analyzed the amount of fibroblasts and number of vessels in wounds experimentally induced in rabbits after treatment with and without association of biomaterials and RSV. The hypothesis is that the topical use of a lipid-lowering drug associated with a biomaterial may increase the amount of fibroblasts and angiogenesis after experimentally induced injury, thereby increasing collagenization to produce a more homogeneous scar. It was found that the association of PRF and RSV promoted an additive effect, increasing angiogenesis by 135%. The use of RSV alone also provided a 77% increase in the amount of fibroblasts. It was concluded that both PRF and RSV have good healing effects, such that the association between them was beneficial and demonstrated a possible additive effect.